The effects of the Islamic Jurisprudence Rule ((لا ضرر ولا ضرار)) on our life: أثر القاعدة الفقهية ((لاضرر ولا ضرار)) في حياتنا - Khan, Noman Ali; Alam , Mohammad Ishaq (Al Khadim Research Journal of Islamic Culture and Civilization, 2024)
This paper highlights the importance of the rules of Islamic jurisprudence specially the rule ((لا ضرر ولا ضرار)) ((there should neither be harming nor reciprocating harm)). They help Islamic scholars in performing their primary responsibility which is to interpret and apply these rules to contemporary issues and challenges faced by Muslims worldwide. Each of these rules makes learning Fiqh easy upon the learner because it summarizes and condense numerous issues under one simple rule. In this paper, it is tried to indicates how the rule ((((لا ضرر ولا ضرار impacts our life matters whether they are religious, or social like marital life, or economical etc.